The Concept of Farming Schools and Branding Digital Agrotourism for Farmer Communities and Students English Department - Suhono, Suhono; Haikal, Haikal; Sari, Yeasy Agustina; Safitri, Linda; Khamid, Abdul; Fajar, Arif (Bulletin of Science Education, 2023)
The article gave an assistance to develop Farmer Schools Karangerjo and Students English Department of Universitas Ma’arif Lampung in order to improve skills and provide an understanding of agricultural management, namely the concept of agricultural mechanization. Hence, they can get access to learning about agricultural management for free and sustainably. Improving the skills and creativity of the farming community in building a roadmap for the digital marketing media movement. it would have an impact on the ability of farmer groups to recognize and utilize online digital media. The method used Asset Based Community Development (ABCD). This assistance has a significant impact on the solidarity of the farmer group community. From the various activities that have been carried out, some farmers have been creative in utilizing the vacant land yards around their yards for vegetable farming activities, in addition to the availability of a PVC pipe irrigation system, which was one of the outcomes of the agricultural mechanization concept. They also apply the concept of organic farming by preparing superior seeds that have been sown properly, from preparing the land to planting vegetable seeds. In addition, there was online digital media, namely Instagram, to improve the skills and creativity of the farming community in building a roadmap for the digital marketing media movement. Keywords: Farming School, Branding Digital, Digital Media Marketing